The Roundtable on Sustainable Palm Oil's national interpretation process in Ecuador: 'Fitting' global standards into local contexts. (October 2019) - Johnson, Adrienne
Abstract: National Interpretation (NI) procedures as linked to roundtable environmental governance mechanisms play important roles in the local substantiation and adoption of global standards. In the case of the Roundtable on Sustainable Palm Oil (RSPO), these under-examined processes of diffusion which I term, 'proto-institutional' procedures', are significant because they introduce global norms to local contexts and assist local actors in making the standards legible. Additionally, they enable local actors to attach meaning to the norms while helping to generate the transformative capacity of the standards. Successful institutionalization is dependent on an appropriate 'institutional fit' between the standards and locality, and more importantly, the social processes that facilitate the local legitimation of the standards. However, uneven power dynamics of the institutionalizing processes may cause NI procedures to be organized in such a way where only a few powerful interests are represented. Using the case of the NI process in Ecuador as its focus, this paper examines the extent to which technical, cultural, and political aspects of the RSPO's NI process connect or 'fit' with the local context. It argues that proto-institutional procedures can create uneven consensus within adopting contexts, and can thereby reinforce and perpetuate existing patterns of exclusion through their domestic uptake and implementation. Furthermore, the paper argues that more attention should be directed to NI processes as more palm-oil producing countries engage in RSPO certification. The paper concludes with suggestions on how the RSPO's NI process can be improved in order to forge more participative and representative procedures. Highlights: National Interpretations are under-examined in roundtable governance literature. Successful local legitimation of global standards is dependent on institutional fit. NI procedures are inflected with, and occur within, contested power relations.